Neuromuscular ultrasound competency assessment: Consensus‐based survey. Issue 5 (13th January 2021) - Tawfik, Eman A.; Cartwright, Michael S.; Grimm, Alexander; Boon, Andrea J.; Kerasnoudis, Antonios; Preston, David C.; Wilder‐Smith, Einar; Axer, Hubertus; Hobson‐Webb, Lisa D.; van Alfen, Nens; Crump, Nicholas; Shahrizaila, Nortina; et al.
Abstract: Neuromuscular ultrasound is a rapidly evolving specialty with direct application for patient care. Competency assessment is an essential standard needed to ensure quality for practitioners, particularly for those newly acquiring skills with the technique. Our aim was to survey experts' opinions regarding physician competency assessment of neuromuscular ultrasound and to identify minimal competency of knowledge and skills. The opinions of 18 experts were obtained through the Delphi method using two consecutive electronic surveys. A high degree of consensus was achieved on items regarding framework and the conduct of neuromuscular ultrasound assessment and the knowledge and skills that a candidate needs to attain minimal competency in neuromuscular ultrasound. In this study, a group of neuromuscular ultrasound experts developed a general framework for neuromuscular ultrasound competency assessment and recommended testable areas of knowledge and skills suitable for establishing minimal competency. Abstract : See Editorial on pages 625–627 in this issue .